Enhanced audiovisual integration with aging in speech perception: a heightened McGurk effect in older adults - Sekiyama, Kaoru; Soshi, Takahiro; Sakamoto, Shinichi (Frontiers in Psychology, 2014)
Two experiments compared young and older adults in order to examine whether aging leads to a larger dependence on visual articulatory movements in auditory-visual speech perception. These experiments examined accuracy and response time in syllable identification for auditory-visual (AV) congruent and incongruent stimuli. There were also auditory-only (AO) and visual-only (VO) presentation modes. Data were analyzed only for participants with normal hearing. It was found that the older adults were more strongly influenced by visual speech than the younger ones for acoustically identical signal-to-noise ratios (SNRs) of auditory speech (Experiment 1). This was also confirmed when the SNRs of auditory speech were calibrated for the equivalent AO accuracy between the two age groups (Experiment 2). There were no aging-related differences in VO lipreading accuracy. Combined with response time data, this enhanced visual influence for the older adults was likely to be associated with an aging-related delay in auditory processing.